Health Literacy Toward Zoonotic Diseases Among Livestock Farmers in Vietnam - Khuong Cao Ba; Jaranit Kaewkungwal; Oranut Pacheun; Uyen Nguyen Thi To; Saranath Lawpoolsri (SAGE Publishing, 2020)
Background: Zoonoses are an increasing concern worldwide, particularly in low- and middle-income countries. People with close contact with animals are at high risk for contracting and transmitting the zoonotic diseases. Objectives: To determine health literacy of livestock farmers toward biosecurity to prevent zoonotic diseases. Methods: This cross-sectional mixed-methods study was conducted in Thai Nguyen Province, Vietnam, where livestock and farming are the main occupation. The questionnaire survey was submitted to 218 farmers who have close contact with livestock. In addition, 8 farmers were invited to an in-depth interview to further explore the health literacy. Results: Half of the participants were men. The average age (standard deviation) of the participants was 49.3(11.5) years. The median years with experience in farming was 15 years. The majority (82.0%) of the participants had moderate health literacy level regarding zoonoses. Improper use of antibiotics was referred by 58.0% of participants, including antibiotic use as feeding supplements (34.0%) and the use of human antibiotics to treat sick animals (24.0%). Many participants were unaware of zoonotic prevention measures and due to this had practices such as not wearing protective equipment (60.0%), an absence of acaricides to prevent vector infestations (52.0%), an absence of disinfection measures (42.0%), low rate of rabies vaccination (54.0%), and do not quarantining sick animals (38.0%). In-depth interviews revealed great concern among farmers about a collective lack of participation from local veterinarians, health workers, and government authorities in zoonoses-prevention efforts. Statistical models showed that farm scale, ethnic groups, and perceived income were associated with the overall health literacy about zoonoses. Conclusion: Comprehensive health education related to zoonotic diseases is recommended to improve overall knowledge, including routes of transmission, symptoms and consequences of diseases, and antibiotic usage. In addition, guidance should be provided to farmers on how to treat sick animals, the appropriate use of antibiotics, and waste management. Local veterinarians and health workers are important contact points and should work closely with the farmers to prevent zoonotic diseases.